Physician associate/assistant contributions to cancer diagnosis in primary care: a rapid systematic review - Jessica Sheringham; Angela King; Ruth Plackett; Anwar Khan; Michelle Cornes; Angelos P. Kassianos (BMC, 2021)
Abstract Background Symptom recognition and timely referral in primary care are crucial for the early diagnosis of cancer. Physician assistants or associates (PAs) have been introduced in 18 healthcare systems across the world, with numbers increasing in some cases to address primary care physician shortages. Little is known about their impact on suspected cancer recognition and referral. This review sought to summarise findings from observational studies conducted in high income countries on PAs' competence and performance on processes concerned with the quality of recognition and referral of suspected cancer in primary care. Method A rapid systematic review of international peer-reviewed literature was performed. Searches were undertaken on OVID, EMBASE, Web of Science, and CINAHL databases (2009-2019). Studies were eligible if they reported on PA skills, processes and outcomes relevant to suspected cancer recognition and referral. Title and abstract screening was followed by full paper review and data extraction. Synthesis of qualitative and quantitative findings was undertaken on three themes: deployment, competence, and performance. Preliminary findings were discussed with an expert advisory group to inform interpretation. Results From 883 references, 15 eligible papers were identified, of which 13 were from the USA. Seven studies reported on general clinical processes in primary care that would support cancer diagnosis, most commonly ordering of diagnostic tests (n = 6) and referrals to specialists (n = 4). Fewer papers reported on consultation processes, such as examinations or history taking (n = 3) Six papers considered PAs' competence and performance on cancer screening. PAs performed similarly to primary care physicians on rates of diagnostic tests ordered, referrals and patient outcomes (satisfaction, malpractice, emergency visits). No studies reported on the timeliness of cancer diagnosis. Conclusion This review of peer-reviewed literature combined with advisory group interpretation suggests the introduction of PAs into primary care may maintain the quality of referrals and diagnostic tests needed to support cancer diagnosis. It also highlights the lack of research on several aspects of PAs' roles, including outcomes of the diagnostic process.